Public policy in universities’ science development: stages of lifecircle - D. Y. Znamenskiy (Управление)
The subject of the study is the policy of the Russian Federation to manage the scientific potential of higher education. The purpose of this article is to identify and characterize the trends in modern public policy in this area. As a basic method of research, a system-dynamic approach to policy research is used that involves the allocation of spatial, temporal and technological components. At the same time, the author focuses on the temporary component of the state policy for managing the scientific potential of higher education, which is revealed through the characterization of various stages of its life cycle. Primary data were obtained as a result of an in-depth expert questionnaire, as well as a focus group interview.The main theoretical result of the study is to substantiate the category “life cycle of public policy”, covering such major stages as its formation, implementation and evaluation. It is proved that each stage corresponds to a certain type of assessment of the scientific potential of higher education: factor, performance and final. The article gives an original approach to the research of the life cycle of the state policy on management of the scientific potential of the higher school, the interrelation of its stages and stages of the life cycle of the most scientific potential of the higher school is grounded.The main empirical result of the study is the identification of the main risks in the processes under consideration and an analysis of the specific influences of various public and political organizations on their formation. The practical significance of the results obtained is conditioned by the possibility of their use in the development of the concept of state policy for the development of university science.